2005
DOI: 10.1590/s0004-282x2005000200027
|View full text |Cite
|
Sign up to set email alerts
|

Distal posterior inferior cerebellar artery aneurysm: case report

Abstract: -The majority of posterior inferior cerebellar artery (PICA) aneurysms are usually found on the bifurcation of the vertebral artery (VA) -PICA junction. Aneurysms arising from more peripheral PICA segments named distal PICA aneurysm are uncommon. The major clinical manifestation is that of an intracranial bleeding and the site of hemorrhage is related to the PICA segment originating the aneurysm. Lesions originating from distal PICA segments, particularly those arising from the telovelotonsillar segment, are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…30 In addition, although intracranial aneurysms usually arise from arterial bifurcations, many distal PICA aneurysms are unrelated to the branching. 15,29 Intracranial aneurysms associated with a DOPICA have been previously reported. 2,3 Lesley et al concluded that the DOPICA has an increased association with intracranial aneurysmal disease and might represent a risk factor for subsequent development of intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…30 In addition, although intracranial aneurysms usually arise from arterial bifurcations, many distal PICA aneurysms are unrelated to the branching. 15,29 Intracranial aneurysms associated with a DOPICA have been previously reported. 2,3 Lesley et al concluded that the DOPICA has an increased association with intracranial aneurysmal disease and might represent a risk factor for subsequent development of intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 98%
“…The PICA is the largest branch of the VA, generally arising 10 mm superior to the foramen magnum, starting from the posterolateral side of the VA and running from the medulla oblongata to the posterior side. 14 In most cases (85-95%), the PICA arises from the intracranial portion of the VA. 15 Beginning from the proximal side, the PICA is divided into five segments (anterior medullary, lateral medullary, tonsillomedullary, telovelar tonsillar and cortical). 16 The PICA shows many variations in morphology and course.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the way of spreading, she vascularizes caudal medulla oblongata, cerebellar tonziles, lowejr portion of cerebellar hemisphere and vermis and plexus horoideus of IV ventricle. 4,5,7 Critical surgical points on the occasion of preparation of aneurysms of this flow are n. IX, n. X and n. XII, whose little traction brings to difficult problems of disfagy, disartry type and potential life endangering aspiration.…”
Section: Discussionmentioning
confidence: 99%